DETERMINAN PERTUMBUHAN LABA: STUDI KASUS PADA PERUSAHAAN MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Ulum, Miftahul; Setiawan, Yuyun Vina; Octavia, Ayu Nurafni (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
The purpose of this study is to analyze the effect of the Current Ratio, Total Asset Turnover, and Net Profit Margin on profit growth in food and beverage companies listed on the Indonesia Stock Exchange. The population in this study consists of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. The results of this study indicate that the Current Ratio, Total Asset Turnover, and Net Profit Margin jointly (simultaneously) have a positive and significant effect on profit growth. Partially, only the Net Profit Margin has a positive and significant effect on profit growth, while the Current Ratio and Total Asset Turnover do not have a significant effect on profit growth. The Current Ratio, Total Assets Turnover, and Net Profit Margin have an influence of 9.0% on Profit Growth, while 91.0% is influenced by other variables not examined